THE MEASUREMENT OF CEFOTAXIME SODIUM IN RAT PLASMA AFTER ORAL ADMINISTRATION: A SENSITIVE HPLC-UV METHOD - Arafat, Mosab; Kon, Svetlana Golocorbin; Mikov, Momir (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: To develop and validate a high-performance liquid chromatographic method for the determination of cefotaxime sodium (NaCTX) concentration in rat plasma. Methods: The method used direct injection of the plasma supernatant after deproteinization with perchloric acid. Degradation of NaCTX in acidic medium during sample treatment was retarded by reducing the strength of perchloric acid to 30%, followed by adding 0.55M of aqueous disodium hydrogen orthophosphate buffer before centrifuging the sample. The mobile phase used was consisted of 0.04M aqueous ammonium acetate: acetonitrile: tetrahydrofurane (90:7:3, v/v) with pH adjusted to 5.7 using glacial acetic acid. The flow rate was 0.9 ml/min, UV detector set at 254 nm and samples were quantified using peak area Results: A well-resolved NaCTX peak and free of interference from endogenous compounds in rat plasma were achieved. Recovery of NaCTX was satisfactory over the concentration range tested 0.125-10 µg/ml. limit of quantification (LOQ) of this assay was 0.125 µg/ml and, at this concentration, intra-and inter-day CV were 5.33 and 6.13 %, respectively. NaCTX was found to be stable in rat plasma after storage at-80 °C, over 90 days. The plasma concentration-time profile in rats for NaCTX after oral administration of NaCTX solution was achieved using the present method. Conclusion: The stability, sensitivity, specificity and reproducibility of this method make it suitable for the determination of NaCTX plasma concentration in pharmacokinetics and bioavailability studies.